(untitled) (Research, Society and Development, 2025)
The objective of this study was to present a literature review on the phytochemical composition of the plant and its main pharmacological properties, with an emphasis on its phytotherapeutic use in the management of anxiety and insomnia, contributing to the rational and safe use of this important medicinal species. The research was conducted in the PubMed, Scielo, ScienceDirect, and Google Scholar databases, considering articles published between 2021 and 2025. The screening resulted in the selection of nine studies that met the previously established eligibility criteria. The results indicated that V. officinalis acts primarily as a modulator of the GABAergic system, promoting an anxiolytic and mild sedative effect, in addition to demonstrating antioxidant activity attributed to the presence of flavonoids and phenolic compounds. The use of this species showed significant efficacy in improving sleep quality and reducing anxiety levels, presenting a low incidence of adverse effects, generally restricted to mild drowsiness or gastrointestinal discomfort. Compared to synthetic drugs, V. officinalis demonstrated a safer and more tolerable profile, being recognized as a traditionally used phytomedicine. However, the heterogeneity of the formulations and the lack of standardization of the extracts used in the studies limit the generalization of the results. It is concluded that Valeriana officinalis represents a promising therapeutic alternative in the treatment of mild anxiety and sleep disorders, highlighting the need for new randomized and controlled clinical trials with phytochemical standardization.